2018
DOI: 10.1007/s00393-018-0426-5
|View full text |Cite
|
Sign up to set email alerts
|

Impact of vitamin D deficiency on clinical parameters in treatment-naïve rheumatoid arthritis patients

Abstract: A significant association was observed between levels of vitamin D and parameters of disease, including body mass index (BMI), DAS28, Th17 cell counts, Treg cell counts, and presence of anti-CCP antibody in RA patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 31 publications
2
11
1
Order By: Relevance
“…Associations between 1,25(OH) 2 D and disease activity in early RA are rarely assessed in human studies. Our finding of a negative association between 1,25(OH) 2 D and DAS28 is in agreement with the findings of Liu et al in 208 treatment naïve RA patients. In 206 early, inflammatory poly‐arthritis patients treated with DMARD up to 6 weeks, Patel et al finds significant inverse associations between baseline 25OHD and NTJ, CRP, HAQ and DAS28‐CRP, whereas the only association regarding 1,25(OH) 2 D was for the HAQ‐score.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Associations between 1,25(OH) 2 D and disease activity in early RA are rarely assessed in human studies. Our finding of a negative association between 1,25(OH) 2 D and DAS28 is in agreement with the findings of Liu et al in 208 treatment naïve RA patients. In 206 early, inflammatory poly‐arthritis patients treated with DMARD up to 6 weeks, Patel et al finds significant inverse associations between baseline 25OHD and NTJ, CRP, HAQ and DAS28‐CRP, whereas the only association regarding 1,25(OH) 2 D was for the HAQ‐score.…”
Section: Discussionsupporting
confidence: 93%
“…40 The association of 1,25(OH) 2 D with CRP and ACPA and of 25OH 2 D with NTJ add credit to the notion that the level of vitamin D metabolites may influence on diagnostic specificity and sensitivity associated with the ACR/ EULAR2010 classification criteria for RA. 26 Although, other studies evaluating vitamin D and ACPA departs from our results: Liu et al 32 found a negative association between ACPA and 25OHD, and similarly, Kerr et al 41 found association between low levels of 25OHD and ACPA positivity in multivariate analyses. On the contrary, Feser et al 42 found no association between 25OHD and ACPA in subjects susceptible to RA.…”
Section: Discussioncontrasting
confidence: 82%
See 2 more Smart Citations
“…As the bioavailability and biological activity of 25(OH)D is dependent on the circulating levels of VDBP with 85% of 25(OH)D being bound to VDBP(18), we tested VDBP levels in the same samples to determine whether the levels of this glycoprotein followed a similar pattern to the free 25(OH)D that were measured. This analysis showed that VDBP levels remained stable over time Circulating 25(OH)D concentrations in RA patients are known to be associated with the presence of ACPA and RF (25,26). However, current evidence is conflicting on the role of 25(OH)D and vitamin D during the preclinical stages of RA (27,28).…”
Section: Effect Of Storage Time and Seasonal Variation On Circulatingmentioning
confidence: 90%